2010
DOI: 10.1007/s10552-010-9577-7
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption and risk of ovarian cancer

Abstract: Overall, our findings provide some support for the hypothesis that tea consumption reduces the risk of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Four case-control studies measuring the effects of green tea on EOC incidence were reported [44][45][46]61].…”
Section: Effect Of Green Tea Intake On Eoc Occurrencementioning
confidence: 99%
See 2 more Smart Citations
“…Four case-control studies measuring the effects of green tea on EOC incidence were reported [44][45][46]61].…”
Section: Effect Of Green Tea Intake On Eoc Occurrencementioning
confidence: 99%
“…Consumption of at least one cup of tea daily was inversely associated with the occurrence of EOC (OR: 0. 46 These four observational studies [44][45][46]61] contain several limitations. It is first difficult to compare them because different definitions of tea intake have been used throughout the studies (e.g.…”
Section: Effect Of Green Tea Intake On Eoc Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…The same authors conducted a meta-analysis and found a non-significant inverse association between green tea intake of $ 1 cup/day and ovarian cancer (OR 5 0.58). 61 The protective effect of green tea intake against ovarian cancer may be stronger in post-diagnosed women. Zhang et al 62 conducted a prospective cohort, following postdiagnosed women for at least 3 years.…”
Section: Epidemiologymentioning
confidence: 99%
“…in the initiation phase and the promotion phase. The consumption of green tea reduces the risk of development of several cancers including colon, breast, ovarian, prostate and lung cancer [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%